Sportswashing and Soft Power: A Critical Analysis of Saudi Arabia's Strategic Use of Global Sport Events to Reconstruct Its International Image - Challa, Karthik Koundinya (Auckland University of Technology, 2026)
The concepts of sportswashing and soft power have gained prominence as contested theories for understanding the practice of sport event diplomacy in the context of state-sponsored sports events in the contemporary geopolitical world. This study explores the ways in which the kingdom of Saudi Arabia uses global sports events as a tool for creating a new image for the country as a modern nation and for practicing soft power by employing Vision 2030 as a key tool for national transformation. This study also delves into how the practice of sportswashing and soft power have been framed and contested through Western media, regional media, and social media, particularly with regard to its practice in the context of Saudi Arabian sport event diplomacy and its global implications for sports politics and human rights discourse. This study employs a qualitative methodological approach for its research, drawing upon an interpretivist research paradigm. The theory of Soft Power as conceptualized by Nye (2004) and Critical Discourse Analysis as conceptualized by Fairclough (1992) have been employed as a theoretical framework for this study. Netnography as a qualitative methodological approach has been utilised for gathering data comprising Western news articles, regional news articles, YouTube videos and comments. Subsequently, Braun and Clarke’s six-phase thematic analysis and NVivo 15 was employed for data analysis and management. The findings reveal four interlinked mechanisms by which Saudi Arabia utilises sport events, including domestic nation-building, international prestige, cultural authenticity, and multi-sport event saturation strategy. The research reveals a significant distinction between Western understandings of sportswashing, which are driven by human rights issues, and regional understandings of development that are driven by economic change. The online space is characterised by contested discourse, where multiple interpretive frameworks exist simultaneously. The inclusion of Vision 2030 is revealed to have limited efficacy for Western audience perception, while being effective for domestic legitimacy and commercial credibility. Thus, the study discovers that sportswashing and soft power are weaponized forms of discourse, rather than analytical tools. Overall, this research reveals that Saudi Arabia's utilisation of sports event strategy is effective for generating domestic pride and international prestige yet continues to face legitimacy challenges within Western discourse. This is a significant revelation, highlighting tensions between competing understandings of truth regarding state-sponsored sporting investments.